Anatomy and Variants of the Triangular Fibrocartilage Complex and Its MR Appearance at 3 and 7T - Nöbauer-Huhmann, Iris-M.; Pretterklieber, Michael; Erhart, Jochen; Bär, Peter; Szomolanyi, Pavol; Kronnerwetter, Claudia; Lang, Susanna; Friedrich, Klaus M.; Trattnig, Siegfried (Seminars in Musculoskeletal Radiology, 2012)
Due to the small size and complexity of its constituents, the triangular fibrocartilage complex (TFCC) has been a challenging structure for magnetic resonance (MR) imaging. Higher-field MR units, at 3T and 7T, with increased spatial resolution and the development of novel MR sequences, are promising tools for an improved visualization of the ulnocarpal complex. Anatomically, the TFCC consists of the TFC proper, the ulnomeniscal homolog, the ulnar collateral ligament, the ulnotriquetral and ulnolunate ligament, and radioulnar ligaments at the volar (palmar) and the dorsal side, as well as the sheath of the extensor carpi ulnaris tendon and the capsule of the distal radioulnar joint. This article describes the normal anatomy of the TFCC and its appearance on high-field MRI. Anatomical variants, such as the positive ulnar variance, and changes during pronation and supination are addressed.
Keywords: triangular fibrocartilage complex; TFCC; anatomy; 7 Tesla; MRI